Patellar tendon complaints and shear wave velocity patterns in maturing alpine skiers - Jonas Hanimann; Daniel P. Fitze; Tobias Götschi; Melanie Gloor; Eling D. de Bruin; Katrien de Bock; Reto Sutter; Jörg Spörri (Bern Open Publishing, 2024)
Introduction Patellar tendinopathy is frequent in adolescent athletes and particularly accentuated in competitive alpine skiers (Fröhlich et al., 2020). Tendinopathies are characterized by long disease histories, and whether they can be healed completely is an open question (Kettunen et al., 2002). Three-dimensional (3D) shear wave elastography (SWE) has proven valuable in the early detection of tendinopathies (Götschi et al., 2023). The aims of this study were to (1) describe the longitudinal progression of patellar tendon complaint prevalence in competitive alpine skiers during adolescence, (2) compare the SWV patterns of skiers that were symptomatic four years ago with those with no history of patellar tendon complaints and (3) analyse whether shear wave velocity (SWV) average values correlate with SWV coefficient of variation (CV). Methods Forty-seven subjects were analysed in this 4-year follow-up study regarding their patellar tendon complaints and SWV patterns. Symptomatic and asymptomatic skiers were identified by clinical examinations including the criteria of pain sensation under loading and palpation-induced pain. SWV was determined by ultrasound-based 3D SWE. Prevalence differences were assessed using Pearson's χ2 tests. Group differences in the SWV patterns were analysed using unpaired sample t tests. Correlations between SWV average and CV values were analysed by means of Pearson's correlation coefficient. Results With proceeding adolescence, the prevalence of patellar tendon complaints significantly decreased from 29.8% at baseline assessment (13-16 years) to 12.7% at follow-up assessment (Pearson's χ2 = 9.429; p = 0.002). Those skiers who were symptomatic at baseline but asymptomatic at the follow-up still had lower average SWV values and higher CVs than asymptomatic skiers with no history of patellar tendon complaints (p = 0.054 and p = 0.011, respectively). Furthermore, there was a significant negative correlation between the tendon SWV average values and their CVs (R = -0.55; p < 0.001). Discussion/Conclusion Despite the decreasing prevalence of patellar tendon complaints in youth competitive alpine skiers after their growth spurt, structural abnormalities appear to remain in asymptomatic subjects with a previous history of patellar tendinopathy, indicating potential long-term implications for mechanical tendon proprieties. The SWV average and CV values were negatively correlated, which underlines our hypothesis that a low SWV is associated with a high CV. This altogether may reflect the degenerative processes in patellar tendons affected by complaints in the early stages of a sports career. References Fröhlich, S., Peterhans, L., Stern, C., Frey, W. O., Sutter, R., & Spörri, J. (2020). Remarkably high prevalence of overuse-related knee complaints and MRI abnormalities in youth competitive alpine skiers: A descriptive investigation in 108 athletes aged 13-15 years. BMJ Open Sport & Exercice Medicine, 6(1), Aticle e000738. https://doi.org/10.1136/bmjsem-2020-000738 Götschi, T., Franchi, M. V., Schulz, N., Fröhlich, S., Frey, W. O., Snedeker, J. G., & Spörri, J. (2023). Altered regional 3D shear wave velocity patterns in youth competitive alpine skiers suffering from patellar tendon complaints - A prospective case-control study. European Journal of Sport Science, 23(6), 1068-1076. https://doi.org/10.1080/17461391.2022.2088404 Kettunen, J. A., Kvist, M., Alanen, E., & Kujala, U. M. (2002). Long-term prognosis for jumper's knee in male athletes. A prospective follow-up study. The American Journal of Sports Medicine, 30(5), 689-692. https://doi.org/10.1177/03635465020300051001